A study of the common constructions with loss and gain in vietnamese- english translation (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis conducts a research on the common constructions with loss and gain in Vietnamese- English Translation. The paper is divided into five chapters. The analysis is made on a bilingual presentation of the translation- Vietnamese is the source language and English is the target language. Firstly, from the findings, the researcher describes the cases of loss and gain then analyzes them and points out their common constructions. In addition, the factors creates loss and gain, the impacts of this phenomenon and how we can apply the common constructions of loss and gain in Vietnamese- English translation are also mentioned in this thesis. The findings, it is hoped, will contribute to the research, the practice, the teaching and studying of Vietnamese- English translation.